Job satisfaction and transformational leadership as the antecedents of OCB role definitions: The moderating role of justice perceptions - Kayaalp, A.; Page, K.; Gumus, O. (International Journal of Business Science and Applied Management, 2021)
Despite the growing acceptance of Organizational Citizenship Behaviors (OCBs), or the "good soldier syndrome", as discretionary and therefore not enforceable individual behaviors, it is becoming increasingly clear that OCB role definitions must be taken into account. The current study examined the antecedents of OCB role definitions in a military work context. Integrating social exchange and role theories, we found that job satisfaction and transformational leadership are related to how broadly subordinates define their jobs and that procedural justice has a moderator role in the relationship between transformational leadership and OCB. Implications for practice and research are discussed.